PENERAPAN ERP PADA PERUSAHAAN MANUFAKTUR UNTUK PERHITUNGAN KPI DAN PENGANGGARAN (STUDI PADA PT ABC MANUFAKTUR 2018) - Sekti, Binastya Anggara (Lembaga Penerbitan Universitas Esa Unggul, 2018)
Information systems that are not yet integrated are very likely to occur in the event of delays in obtaining information or losing important information, which can cause delays and even execution errors, which can have a small to large impact on company losses. ERP (enterprise resource planning) is a system that is developed to manage data or information in a company to integrate and automate business processes in large manufacturing activities / operations (factories), light manufacturing (assembling), trading, logistics, distribution, finance, and human resources. PT ABC Manufaktur is an export-oriented medium-scale manufacturing company that has implemented SAP since 2004. Over time, due to changes in the global market, where the 2008 economic crisis and the global crisis in 2012 occurred, the company made changes in the business and added to its portfolio. product. This is an effort to continue to exist in increasingly fierce business competition, especially to face global competitors, including China and other producing countries. As a result of these changes, in 2012 the company made many business changes and in 2017 it was necessary to re-implement SAP by transforming the company's activities into several business units. ERP implementation is an ideal choice for all types of manufacturing companies because in manufacturing companies are generally capital intensive and labor intensive, where all resources must be managed well, effectively and efficiently. After re-implementation, the company can calculate KPI and budgeting on each business unit and department more accurately than before implementation. The purpose of this research is to be able to utilize ERP in addition to information system integration, it can also be used to build KPI calculations (Key Performance Indicators), reward & punishment and budgeting with more accurate and realtime. The results showed that the calculation of KPI, reward & punishment, as well as budgeting in certain production periods can be done accurately, so that it can provide motivation for the workers and make good budget planning for the company.Ã‚Â Keyword : SAP, KPI, Budgeting